Validation of the Pocket Book for Assessment of Students with Special Needs at Special Schools in Tanah Datar Regency - Yoselisa, Dani -; Fitriani, Wahidah; Rahayu, Sri Putri; Ahmad, Mutia Aini (Al-Qalb : Jurnal Psikologi Islam, 2024)
Every Special School (SLB) requires appropriate assessments that are appropriate to the conditions of the students so that educational goals for children with special needs can be achieved. Assessments are needed to classify students according to their problems, so that they can be used as material for consideration in designing learning programs. Students at Special Schools (SLB) who have not implemented appropriate assessments receive programs or services in their learning that do not meet the student's needs. Initial research conducted at Special Schools in Kab. Tanah Datar found that there was no standard assessment used by the school in classifying students and creating learning programs for students with special needs. Determination of students at school based on age grouping. This research aims to develop a pocket book to assist SLB teachers in carrying out initial assessments of students with special needs. The method used in this research is Research and Development (RAD) with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The research produced an instrument in the form of a pocket book based on a behavior checklist which can detect students who have special needs by taking 3 classifications of Children with Special Needs, namely ADHD, Autism and Mentally Impaired. The results of this research show that pocket books can be understood and used by teachers to help teachers carry out initial assessments of students and group students in special schools in Tanah Datar Regency.